The vacuolar calcium sensors CBL2 and CBL3 affect seed size and embryonic development in Arabidopsis thaliana. (12th March 2014) - Eckert, Christian; Offenborn, Jan Niklas; Heinz, Tobias; Armarego‐Marriott, Tegan; Schültke, Stefanie; Zhang, Chunxia; Hillmer, Stefan; Heilmann, Mareike; Schumacher, Karin; Bock, Ralph; Heilmann, Ingo; Kudla, Jörg
Summary Stimulus‐specific calcium (Ca2+) signals have crucial functions in developmental processes in many organisms, and are deciphered by various Ca2+‐binding proteins. In Arabidopsis thaliana, a signaling network consisting of calcineurin B‐like (CBL) protein calcium sensors and CBL‐interacting protein kinases (CIPKs) has been shown to fulfil pivotal functions at the plasma membrane in regulating ion fluxes and abiotic stress responses. However, the role of tonoplast‐localized CBL proteins and especially their function in regulating developmental programs remains largely unknown. In this study, we analyzed single and double mutants of the closely related tonoplast‐localized calcium sensors CBL2 and CBL3, which show either reduction of function (rf) or complete loss of function (lf). While single cbl2 or cbl3 mutants did not display discernable phenotypes, cbl2/cbl3 mutants exhibited defects in vegetative growth and were severely impaired in seed development and morphology. Seeds of the cbl2/3rf mutant were smaller in size and exhibited reduced weight and fatty acid content compared to wild‐type, but accumulation of sucrose was not altered. Moreover, accumulation of inositol hexakisphosphate (InsP6), the major storage form of phosphorus in seeds, was significantly reduced in mutant seeds. In addition, complete loss of CBL2 and CBL3 function in cbl2/3lf resulted in a high frequency of severe defects in embryonic development. Together, our findings reveal a crucial function of Ca2+‐controlled processes at the vacuolar membrane as determinants of seed yield and size, and demonstrate the importance of vacuolar CBL calcium sensors for plant embryogenesis.